Anticoagulation for Acute Ischaemic Stroke?. Issue 1 (1st October 2001) - Kay, Richard
Abstract : INTRODUCTION Six years ago, in December 1955, there appeared in the New England Journal of Medicine an article that revolutionized the way we think of stroke. I am referring, of course, to the NINDS paper 'Tissue plasminogen activator for acute ischemic stroke' (The National Institute of Neurological Disorders and Stroke rt-PA Stroke Study Group 1995), which singularly made the FDA recognize rt-PA as still the only approved treatment for stroke. Trailing behind that landmark paper was our paper from Hong Kong, 'Low-molecular-weight heparin for the treatment of acute ischemic stroke' (Kay et al . 1995), which showed that an anticoagulant, nadroparin, if given subcutaneously within 48 h of stroke onset could also reduce death or disability. This paper temporarily raised the hope that there might be another treatment for stroke than thrombolysis within three hours. But as more anticoagulant trials were completed and published, that hope has evaporated. In this article